EFFECT OF EXCHANGE RATE FLUCTUATION AND ECONOMIC GROWTH IN NIGERIA: 2001 - 2022 (Journal of the Management Sciences, 2024)
This research work examined the effect of exchange rate fluctuation on the economic growth in Nigeria. In specific term, the effect of exchange rate fluctuation on nominal GDP, inflation, and balance of payment was ascertained. The study employed Ordinary Least Square (OLS) regression and the Granger Causality test. The ordinary least square regression method was used to examine the nature of the relationship between the independent and dependent variables. On the other hand, the Granger Causality test examines the effect of one variable on another. This study used secondary time series data from 2001 to 2022. Data on exchange rate, inflation rate, balance of payment, and real gross domestic product were sourced variables have significant impact on each other. However, inflation rate is not impacted by exchange rate fluctuations in Nigeria. The monetary authority should adopt exchange rate policies that regulate the movements of the nominal exchange rate in line with the prevailing target for economic growth. Exchange rate depreciations should also be backed up by other stabilization policies to ensure that it from CBN Statistical Bulletin. The result revealed that exchange rate fluctuation has a positive and significant relationship with nominal GDP and it also has a significant impact on nominal GDP; exchange rate fluctuation has a positive and insignificant relationship with inflation rate in Nigeria; and exchange rate fluctuation has a negative and significant relationship with balance of payment in Nigeria and both has a positive impact on the Nigerian economy. The monetary authorities should unify the foreign exchange market rates to ensure that inflationary targeting is more accurately attained through exchange rate policies and other monetary policies. Such policies could include raising interest rates, unifying exchange rates across all windows, and the adequate supply of forex backed-up with restrictions on its use.
Keywords: Exchange rate fluctuation, nominal GDP, inflation, balance of payment.